Treatment patterns, testing practices, and outcomes in the pre-FLAURA era for patients with EGFR mutation-positive advanced NSCLC: a retrospective chart review (REFLECT). (November 2021) - Addeo, Alfredo; Hochmair, Maximilian; Janzic, Urska; Dudnik, Elizabeth; Charpidou, Andriani; Płużański, Adam; Ciuleanu, Tudor; Donev, Ivan Shterev; Elbaz, Judith; Aarøe, Jørgen; Ott, René; Peled, Nir
Introduction: For epidermal growth factor receptor mutation-positive (EGFRm) non-small-cell lung cancer (NSCLC), EGFR-tyrosine kinase inhibitors (EGFR-TKIs) are the preferred first-line (1 L) treatment in the advanced setting. Osimertinib, a third-generation EGFR-TKI, received full approval in 2017 for second-line (2 L) treatment of EGFR T790M-positive NSCLC. The REFLECT study characterizes real-world treatment/testing patterns, attrition rates, and outcomes in patients with EGFRm advanced NSCLC treated with 1 L first-/second-generation (1G/2G) EGFR-TKIs before 1 L osimertinib approval. Methods: Retrospective chart review (NCT04031898) of European/Israeli adults with EGFRm unresectable locally advanced/metastatic NSCLC, initiating 1 L 1G/2G EGFR-TKIs 01/01/15–30/06/18 (index date). Results: In 896 patients (median follow-up of 21.5 months), the most frequently initiated 1 L EGFR-TKI was afatinib (45%). Disease progression was reported in 81%, including 10% (86/896) who died at 1 L. By the end of study, most patients discontinued 1 L (85%), of whom 33% did not receive 2 L therapy. From index, median 1 L real-world progression-free survival was 13.0 (95% confidence interval (CI): 12.3–14.1) months; median overall survival (OS) was 26.2 (95% CI: 23.6–28.4) months. 71% of patients with 1 L progression were tested for T790M; 58% were positive. Of those with T790M, 95% received osimertinib in 2 L or later. Central nervous system (CNS) metastases were recorded in 22% at index, and 15% developed CNS metastases during treatment (median time from index 13.5 months). Median OS was 19.4 months (95% CI: 17.1–22.1) in patients with CNS metastases at index, 24.8 months (95% CIs not available) with CNS metastases diagnosed during treatment, and 30.3 months (95% CI: 27.1, 33.8) with no CNS metastases recorded. Conclusion: REFLECT is a large real-world study describing treatment patterns prior to 1 L osimertinib availability for EGFRm advanced NSCLC. Given the attrition rates highlighted in the study and the impact of CNS progression on outcomes, offering a 1 L EGFR-TKI with CNS penetration may improve patient outcomes in this treatment setting.